Important soil microbiota's effects on plants and soils: a comprehensive 30-year systematic literature review - Wang, Xueling; Chi, Yongkuan; Song, Shuzhen (Frontiers in Microbiology, 2024)
Clarifying the relationship between soil microorganisms and the plant-soil system is crucial for encouraging the sustainable development of ecosystems, as soil microorganisms serve a variety of functional roles in the plant-soil system. In this work, the influence mechanisms of significant soil microbial groups on the plant-soil system and their applications in environmental remediation over the previous 30 years were reviewed using a systematic literature review (SLR) methodology. The findings demonstrated that: (1) There has been a general upward trend in the number of publications on significant microorganisms, including bacteria, fungi, and archaea. (2) Bacteria and fungi influence soil development and plant growth through organic matter decomposition, nitrogen, phosphorus, and potassium element dissolution, symbiotic relationships, plant growth hormone production, pathogen inhibition, and plant resistance induction. Archaea aid in the growth of plants by breaking down low-molecular-weight organic matter, participating in element cycles, producing plant growth hormones, and suppressing infections. (3) Microorganism principles are utilized in soil remediation, biofertilizer production, denitrification, and phosphorus removal, effectively reducing environmental pollution, preventing soil pathogen invasion, protecting vegetation health, and promoting plant growth. The three important microbial groups collectively regulate the plant-soil ecosystem and help maintain its relative stability. This work systematically summarizes the principles of important microbial groups influence plant-soil systems, providing a theoretical reference for how to control soil microbes in order to restore damaged ecosystems and enhance ecosystem resilience in the future.